2006
DOI: 10.1111/j.1478-3231.2006.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of fusing PET plus CT images in hepatocellular carcinoma and combined hepatocellular and cholangiocarcinoma patients with extrahepatic metastases: preliminary findings

Abstract: The fusion of PET plus CT images is useful in detecting extrahepatic metastases in HCC and combined HCC/CC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 22 publications
(30 reference statements)
0
26
1
Order By: Relevance
“…PET/CT is used in HCC patients to detect extrahepatic metastases (11,17), predict outcome after resection (18,19), select liver transplantation candidates (20), and assess residual tumors after treatment with transcatheter arterial chemoembolization or radiofrequency ablation (21). The usefulness of these applications depends on the ability of PET/CT to detect small or atypical lesions-those for which no diagnostic studies with spiral CT or contrastenhanced MRI are available, those in the liver, and those in extrahepatic areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET/CT is used in HCC patients to detect extrahepatic metastases (11,17), predict outcome after resection (18,19), select liver transplantation candidates (20), and assess residual tumors after treatment with transcatheter arterial chemoembolization or radiofrequency ablation (21). The usefulness of these applications depends on the ability of PET/CT to detect small or atypical lesions-those for which no diagnostic studies with spiral CT or contrastenhanced MRI are available, those in the liver, and those in extrahepatic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty milligrams of furosemide were administered intravenously within 10 min of the 18 F-FDG injection, and then 500 mL of water were given. 18 F-FDG (444-740 MBq [12][13][14][15][16][17][18][19][20]) was injected intravenously 4 h after 11 C-acetate PET/CT. Patients were encouraged to rest during the 18 F-FDG uptake period.…”
Section: Imaging Studies and Biopsymentioning
confidence: 99%
“…However, several studies reported that PET or PET/CT is useful for detection of extrahepatic metastases from HCC [18][19][20][21]. Moreover, PET/CT showed higher sensitivity for the detection of bone metastasis than other extrahepatic metastases from HCC [22].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of staging for Colon, lung, and breast malignancies with PET CT is 92-100% and 85-100% respectively. 30 CT Porto angiography is one of the most sensitive imaging for metastasis but it is an examination that is performed in high selected cases, in few institutions and not for all types of liver lesions. Guided FNA will help identifying the primary lesion.…”
Section: Liver Metastasismentioning
confidence: 99%